Melatonin is a potential inhibitor of ovarian cancer: molecular aspects - Hadis Zare; Rana Shafabakhsh; Russel J. Reiter; Zatollah Asemi (Journal of Ovarian Research, 2019)
Abstract Ovarian cancer is one of the most common causes of morbidity related to gynecologic malignancies. Possible risk factors are including hereditary ovarian cancer, obesity, diabetes mellitus, alcohol consumption, aging, and smoking. Various molecular signaling pathways including inflammation, oxidative stress, apoptosis and angiogenesis are involved in this progression of ovarian cancer. Standard treatments for recently diagnosed patients are Surgery and chemotherapy such as co-treatment with other drugs such that the exploitation of neoadjuvant chemotherapy is expanding. Melatonin (N-acetyl-5-methoxy-tryptamine), an endogenous agent secreted from the pineal gland, has anti-carcinogenic features, such as regulation of estradiol production, cell cycle modulation, stimulation of apoptosis as well as anti-angiogenetic properties, anti-inflammatory activities, significant antioxidant effects and modulation of various immune system cells and cytokines. Multiple studies have shown the significant beneficial roles of melatonin in various types of cancers including ovarian cancer. This paper aims to shed light on the roles of melatonin in ovarian cancer treatment from the standpoint of the molecular aspects.